2019
DOI: 10.3389/fmars.2019.00535
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton and Micronekton Active Flux Across the Tropical and Subtropical Atlantic Ocean

Abstract: Quantification of the actual amount of carbon export to the mesopelagic layer by both zooplankton and micronekton is at present a gap in the knowledge of the biological pump. These organisms perform diel vertical migrations exporting carbon through respiration, excretion, mortality, and egestion during their residence at depth. The role of zooplankton in active flux is nowadays partially assessed. However, micronekton active flux is scarcely known and only a few studies addressed this downward transport. Even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 61 publications
5
65
3
Order By: Relevance
“…M h can be multiplied by the number of hours spent at depth to obtain individual contribution to downward flux attributed to natural mortality. For comparison, we also calculate mortality from growth as in Hernández-León et al (2019). Assuming our systems are in steady-state, growth should be approximately equivalent to mortality.…”
Section: Mortalitymentioning
confidence: 99%
See 3 more Smart Citations
“…M h can be multiplied by the number of hours spent at depth to obtain individual contribution to downward flux attributed to natural mortality. For comparison, we also calculate mortality from growth as in Hernández-León et al (2019). Assuming our systems are in steady-state, growth should be approximately equivalent to mortality.…”
Section: Mortalitymentioning
confidence: 99%
“…While this is the best available correction for our data, it should be noted that our sampling approach differs slightly from that of Koslow et al (1997) in terms of tow speed (1 vs. 1.5 m/s), net dimension (157.5 vs. 105 m 2 ), and mesh size (200 mm tapering to 10 mm at the codend vs. 100 mm tapering to 10 mm at the codend), which may influence the overall net efficiency. Thus, we also apply a more conservative correction for net efficiency of 50% for comparison with other studies in the literature (i.e., Hernández-León et al, 2019). All conversions are shown in Supplementary Table S8.…”
Section: Vertical Migration and Active Carbon Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…Hansen and Visser (2016) estimated that across the North Atlantic active transport by mesozooplankton may constitute 27% of total export. In addition to zooplankton, vertical migrations by micronekton can also lead to significant export fluxes (Angel and Pugh, 2010; Davison et al, 2013; Hernandez-Leon et al). Using biomass estimates and metabolic relationships, Davison et al (2013) found micronekton contributions of 22 – 24 mg C m −2 d −1 (or 15% - 17% of estimated passive export) in the northeast Pacific.…”
Section: Discussionmentioning
confidence: 99%